Semantic Memory Organization in Children and Young Adults - Favarotto, Victoria (2014)
The study of the organization of semantic memory has become of great interest in the cognitive psychology field and in neuropsychological research. Semantic knowledge considered to be represented by concepts, which can be related taxonomically (when they are hierarchically organized) or thematically (when they are linked by cross-categorical relations). Both relations arise from distinct processes, as evidenced by numerous neuropsychological and behavioral dissociations. Many works have stated that the production of thematic relations outnumbers that of taxonomic relations in children, and that as they grow older a thematic-to-taxonomic shift occurs, while others claim that such a shift does not take place and state that one major problem is that the tasks used in previous studies to assess concept-relations are biased. In our work we performed a feature production task in such a way that subjects could freely associate concepts with their features. Our results, using this non-biased-task, show that the evocation of taxonomic relations was higher in the adult group (formed by thirty 20-to 40-year-olds) compared to the children group (formed by forty-eight 6-to 9-year-olds), but that, nonetheless, thematic relations were still present in the adult group. This suggests, instead of a thematic-to-taxonomic shift in adulthood, the coexistence of both types of relations, which is crucial to research on language structure and conceptual knowledge. Thus, our results contribute to the understanding of semantic knowledge organization and provide valuable groundwork to the development of clinical instruments used in neuropsychological tests to assess language, attention and semantic memory, where precise information of concept-relations is crucial.